Direct blood dry LAMP: a rapid, stable, and easy diagnostic tool for Human African Trypanosomiasis. - Kyoko Hayashida (PLoS Neglected Tropical Diseases, 2015)
Loop-mediated isothermal amplification (LAMP) is a rapid and sensitive tool used for the diagnosis of a variety of infectious diseases. One of the advantages of this method over the polymerase chain reaction is that DNA amplification occurs at a constant temperature, usually between 60-65°C; therefore, expensive devices are unnecessary for this step. However, LAMP still requires complicated sample preparation steps and a well-equipped laboratory to produce reliable and reproducible results, which limits its use in resource-poor laboratories in most developing countries. In this study, we made several substantial modifications to the technique to carry out on-site diagnosis of Human African Trypanosomiasis (HAT) in remote areas using LAMP. The first essential improvement was that LAMP reagents were dried and stabilized in a single tube by incorporating trehalose as a cryoprotectant to prolong shelf life at ambient temperature. The second technical improvement was achieved by simplifying the sample preparation step so that DNA or RNA could be amplified directly from detergent-lysed blood samples. With these modifications, diagnosis of HAT in local clinics or villages in endemic areas becomes a reality, which could greatly impact on the application of diagnosis not only for HAT but also for other tropical diseases.